2020
DOI: 10.1200/jco.2020.38.15_suppl.e21664
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogressive disease during treatment with immune checkpoint inhibitors in patients with advanced non-small cell lung cancer (NSCLC).

Abstract: e21664 Background: Hyperprogressive disease (HPD) is a new pattern of progressión during immunotherapy and is described as an acceleration of tumor growth during treatment with immune checkpoint inhibitors (ICI). The rate of HPD in advanced solid tumors remains unknown, but it has been reported in 9% to 29% of patients in two recent series. Our aim was to study prognostic factors of HPD. Methods: We collected data of 104 patients diagnosed of advanced NSCLC and treated with ICI in monotherapy at our instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After screening and eligibility assessment, a total of three prospective and 31 retrospective observational cohort studies involving a total of 4117 patients in 12 countries were included in the systematic review and meta‐analysis (Table S3 ). 4 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 A list of excluded studies from the full‐text screening, with reasons for their exclusion, can be found in Table S4 .…”
Section: Resultsmentioning
confidence: 99%
“…After screening and eligibility assessment, a total of three prospective and 31 retrospective observational cohort studies involving a total of 4117 patients in 12 countries were included in the systematic review and meta‐analysis (Table S3 ). 4 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 A list of excluded studies from the full‐text screening, with reasons for their exclusion, can be found in Table S4 .…”
Section: Resultsmentioning
confidence: 99%